(untitled) (Bangladesh Journal of Agricultural Research, 2015)
A study was conducted at Fruit Research Farm and Postharvest Technology Laboratory of Horticulture Research Centre, Bangladesh Agricultural Research Institute during the period from October 2009 to February 2010 to determine the maturity indices of ber. The ber variety BARI Kul-2 was selected for conducting the study. Ber fruits were tagged at fruit setting stage and harvested at 90, 100, 110, 120 days after fruit set (treatments). The physicochemical characters like fruit weight and size, specific gravity, TSS (%), sugar (%), acidity (%), pulpstone ratio, TSS-acid ratio, sugar-acid ratio as well as subjective sensory attributes like fruit colour and texture, and storage traits like storage life, physiological weight loss (%), ripening status and decay, browning and shriveling (%) of harvested fruits were evaluated for determining the proper stage of commercial maturity. The fruit weight, TSS (%), pulp-stone ratio, TSS/acid ratio, sugar-acid ratio and specific gravity of BARI Kul-2 were found 24.33g, 15.60, 15.66, 39.72, 16.14 and 0.98, respectively, at 110 days after fruit set. Considering all the physical and chemical characters matching with subjective parameters, fruits of BARI Kul-2 was found commercially mature after 110 days of fruit set when the fruits turned into light greenish yellow to greenish yellow colour and specific gravity less than 1.00. Bangladesh J. Agril. Res. 40(1): 163-176, March 2015